Unraveling progressive verbal memory deficits in Huntington’s disease: insights from the LASSI-L - Sierra, Luis A.; Kaur, Japleen; Frank, Samuel A.; Halko, Mark A.; Curiel Cid, Rosie E.; Loewenstein, David A.; Corey-Bloom, Jody; Laganiere, Simon (Frontiers in Neurology, 2025)
Background and objectivesHuntington’s disease (HD) is characterized by progressive cognitive decline, with early deficits often preceding motor symptoms. The Loewenstein-Acevedo Scales for Semantic Interference and Learning (LASSI-L) captures many types of deficits in verbal memory including susceptibility to interference. The current study aims to delineate the progression of these deficits across different stages of HD.Methods151 participants (89 HD, 62 healthy controls) were recruited across three sites. HD participants were classified into three groups using a PIN score and TMS: >10 years from manifest HD, <10 years from manifest HD, and manifest HD. Group comparisons on the LASSI-L were assessed using multiple ANCOVAs adjusting for age, followed by post-hoc pairwise comparisons and a Bonferroni correction.ResultsSequential group differences for susceptibility to interference effects were observed on the LASSI-L. Proactive Semantic Interference (PSI) deficits emerged >10 years before manifest HD, Failure to Recover from PSI (frPSI) emerged <10 years before manifest HD, and in the Manifest HD stage, participants exhibited additional deficits in Retroactive Semantic Interference (RSI). Based on cutoff scores derived from healthy control performance, 98% (87/89) of the HD cohort demonstrated either normal performance or significant impairments, primarily in PSI, with some showing concurrent deficits in frPSI and/or RSI. Furthermore, 88% of participants adhered to the full sequential decline pattern, progressing from deficits in PSI, to frPSI, and then to RSI.DiscussionThe LASSI-L appears to be a useful tool for detecting early and progressive cognitive changes in Huntington’s disease, particularly by capturing the sequential nature of verbal memory deficits, including early vulnerability to interference. These findings suggest that the LASSI-L may help refine HD staging by integrating sequential neuropsychological markers of cognitive decline.